Excessively increased thalamocortical connectivity and poor initial antiseizure medication response in epilepsy patients - Zhong, Jiyuan; Tan, Ge; Wang, Haijiao; Chen, Yangmei (Frontiers in Neurology, 2023)
Objectives: The network mechanism underlying the initial response to antiseizure medication in epilepsy is not revealed yet. Given the central role of thalamus in brain network, we conducted a case-control study to investigate the association between thalamic connectivity and medication response. Methods: We recruited 39 patients with newly diagnosed and medication-naïve epilepsy of genetic or unknown etiology, including 26 with good response (GR-group) and 13 with poor response (PR-group), and 26 matched healthy participants (Control). We measured the grey matter density (GMD) and the amplitude of low-frequency fluctuation (ALFF) of bilateral thalami. We then set each thalamus as the seed region of interest (ROI) to calculate voxel-wised functional connectivity (FC), and assessed ROI-wised effective connectivity (EC) between thalamus and targeted regions. Results: We found no significant difference in GMD or ALFF of bilateral thalami among groups. However, we observed that the FC values of several circuits connecting left thalamus and cortical areas, including bilateral Rolandic operculum, left insula, left postcentral gyrus, left supramarginal gyrus and left superior temporal gyrus, differed among groups (False Discovery Rate correction, P < 0.05), with a higher value in the PR-group than in the GR-group and/or Control (Bonferroni correction, P < 0.05). Similarly, both outflow and inflow EC in each thalamocortical circuit were higher in the PR-group than in the GR-group and Control, although these differences did not survive Bonferroni correction (P < 0.05). The FC showed a positive correlation with the corresponding outflow and inflow EC for each circuit. Conclusion: Our finding suggested that patients with stronger thalamocortical connectivity, potentially driven by both thalamic outflowing and inflowing information, may be more likely to have a poor response to initial antiseizure medication.